PRODUCTION PERFORMANCE AND ECONOMICS OF REARING OF KHAKI CAMPBELL DUCKS IN BACKYARD FARMING SYSTEM IN DARRANG DISTRICT OF ASSAM, INDIA - Angshuman Sarmah; Banasmita Barman; Bipul Kr. Das; Abdul Hafiz (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The production performance and economic viability of Khaki Campbell ducks in backyard farming systems at NICRA-adopted flood-prone village in the Darrang district of Assam was evaluated. The study investigated key productivity metrics such as egg production, growth performance, and survival rates, in addition to economic factors like input costs, labor requirements, and market returns. The findings of the study indicated that Khaki Campbell ducks can perform well in backyard systems, with good egg production and growth rate. The mean body weight at 30 weeks of age was 1.82 kg and the average age at first egg was 163 days. Throughout the study period, the mean egg production was 185.5 and the mean mortality rate was 12.5%. The practice of backyard rearing of Khaki Campbell ducks is viable with a Benefit-Cost ratio of 2.07. The research highlighted the potential of ducks in enhancing household income and nutritional security and contributing to greater agricultural resilience against climate variability. The findings of the research contribute to the broader discourse on sustainable rural development and offers practical recommendations for similar agro-climatic regions facing the dual challenges of agricultural productivity and climate change